Improving memory following prefrontal cortex damage with the PQRST method - Ciaramelli, Elisa; Neri, Francesco; Marini, Luca; Braghittoni, Davide (Frontiers in Behavioral Neuroscience, 2015)
We tested (1) whether the PQRST method, involving Preview (P), Question (Q), Read (R), State (S), and Test (T) phases, is effective in enhancing long-term memory in patients with mild memory problems due to prefrontal cortex lesions, and (2) whether patients also benefit from a more self-initiated version of the PQRST. Seven patients with prefrontal lesions encoded new texts under three different conditions: the Standard condition, requiring to read texts repeatedly, the PQRST-Other condition, in which the experimenter formulated questions about the text (Q phase), and the PQRST-Self condition, in which patients formulated the relevant questions on their own. Compared to the Standard condition, both the PQRST-Other and the PQRST-Self condition resulted in higher immediate and delayed recall rates, as well as a higher ability to answer questions about the texts. Importantly, the two PQRST conditions did not differ in efficacy. These results confirm that the PQRST method is effective in improving learning of new material in brain-injured populations with mild memory problems. Moreover, they indicate that the PQRST proves effective even under conditions with higher demands on patients’ autonomy and self-initiation, which encourages its application to real-life situations.